Batik as a Sustainable Choice: Analysis of Motif and Color Pattern Preferences of Generation Z Consumers on Purchasing Decisions: Batik Sebagai Pilihan Berkelanjutan: Analisis Preferensi Motid dan Corak Warna Konsumen Generasi Z Terhadap Keputusan Pembelian - Rachmadiansyah, Idham Akbar; Nugraha, Paksi Hasyim; Saputra, Savero Ditana Vito; Listyan, Dimas Airul; Sofiansyah, Thoyib (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Generation Z, as individuals who care more about environmental issues and sustainability, play a critical role in sustainability in Indonesia, which encourages them to look for alternative clothing that is fashionable and environmentally friendly. Preserving batik in Generation Z has the potential to reduce negative impacts on the environment and make it an option that is in line with sustainable values. This research examines Generation Z's Batik motif and color pattern preferences in choosing batik products. The population of this research is Generation Z batik consumers, using a non-probability sampling approach in taking samples using a purposive sampling technique and resulting in a sample size of 101 respondents. This type of research is descriptive quantitative using primary and secondary data. The analysis technique used is multiple linear regression using descriptive statistical methods. The results of the analysis show that the independent variables that influence the dependent variable significantly and positively are the batik motif and color pattern variables, but they do not influence them simultaneously or simultaneously.